MENYUSUN PERANGKAT PEMBELAJARAN LKS/LKPD dan INSTRUMEN PENILAIAN - Rakhmania Annur Nina; Nurul Humairah; Sri Wulan; Takdirmin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Learning materials are essential components in supporting the success of the teaching and learning process. Among these materials, Student Worksheets (LKS/LKPD) and assessment instruments play a highly strategic role. The Student Worksheet (LKPD) is one of the learning tools that functions to support the achievement of learning processes and outcomes, and in order to obtain a quality and feasible LKPD, a feasibility assessment must be conducted. This article aims to provide a systematic guide for developing quality LKS/LKPD as well as valid and reliable assessment instruments. The study was conducted through a literature review approach drawing on various relevant scientific sources. The findings indicate that the development of a good LKPD must consider aspects of content feasibility, language, activities, appearance, and presentation. Validation results show that well-developed learning tools, including LKPD, can fall within the valid to highly valid category and are suitable for use in the learning process. Furthermore, authentic assessment covers cognitive, affective, and psychomotor aspects—using techniques such as written tests, oral tests, assignments, observations, self-assessments, peer assessments, projects, performance tasks, and portfolios—to obtain a comprehensive picture of students' competency attainment. This article is expected to serve as a practical reference for educators in designing effective, measurable, and curriculum-aligned learning materials. Keywords: Learning Materials, Student Worksheets, LKS, LKPD, Assessment Instruments, Curriculum